Development of Interactive Powerpoint Media Based on Deep Learning Assisted by Canva Economic Activity Materials in Indonesia Grade 5 - Lailatus Sa’adah; Shofi Nur Amalia; Cindya Alfi (Journal of Practice Learning and Educational Development, 2026)
This article is a development study that explains the development of interactive PowerPoint media based on deep learning assisted by Canva for economic activity materials in Indonesia for fifth-grade. The background for this study stems from the minimal use of technology-based learning media in schools, which has resulted in low student participation in learning. Teachers often rely solely on textbooks and blackboards without utilizing other more engaging media. To address this issue, the researcher developed an interactive PowerPoint presentation based on deep learning with the assistance of Canva. An interactive PowerPoint presentation is an educational medium that supports engaging learning activities, involving interaction between teachers and students as users, thereby helping students become enthusiastic about understanding the material. Deep learning is a learning approach that emphasizes in-depth understanding of concepts and mastery of competencies. Students are encouraged to actively engage in the learning process. The researcher's objective in developing interactive PowerPoint media based on deep learning is to determine the validity and attractiveness of interactive PowerPoint media. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The expert validation results for the media obtained 95%, subject matter experts 97.5%, teacher appeal 95%, and student appeal results.